Hamartoma of the thoracic wall. Issue 4 (July 1972) - Gupta, Saibal; Pal, Narayan C.
Abstract : A 16-year-old boy presented with a slowly growing tumour of the chest wall involving the posterior ends of the second and third ribs on the left side and the corresponding vertebrae. The tumour on excision was a well-localized growth with a bony shell, the second and third ribs originating from its anterior end. Histological studies showed a benign tumour with haphazard distribution of bony spicules, smooth muscle, adipose tissue, angiomatous tissue, nerve bundles, and lymph follicles. This was diagnosed as a hamartoma of the thoracic wall.